2020
DOI: 10.1080/02656736.2020.1714084
|View full text |Cite
|
Sign up to set email alerts
|

Moderate hyperthermic heating encountered during thermal ablation increases tumor cell activity

Abstract: Purpose: The aim of this study was to determine whether moderate hyperthermic doses, routinely encountered in the periablational zone during thermal ablation, activate tumor cells sufficiently to secrete pro-tumorigenic factors that can induce increased proliferation. Material and methods: R3230 rat mammary tumor cells and human cancer cell lines, MCF7 breast adenocarcinoma, HepG2 and Huh7 HCC, and HT-29 and SW480 colon adenocarcinoma, were heated in to 45 ± 1 C or 43 ± 1 C in vitro for 5-10 min and incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
(43 reference statements)
0
25
0
Order By: Relevance
“…It is well known that during thermal ablation, the temperature inside the ablation zone decreases from center to margin where the temperature is sub-lethal and residual viable tumor cells often exist, potentially causing tumor relapse [16,17]. In our previous study, we reported that chronic hypoxia, an important characteristic following TACE, can trigger chemoresistance to doxorubicin in HepG2 cells [18].…”
Section: Introductionmentioning
confidence: 89%
“…It is well known that during thermal ablation, the temperature inside the ablation zone decreases from center to margin where the temperature is sub-lethal and residual viable tumor cells often exist, potentially causing tumor relapse [16,17]. In our previous study, we reported that chronic hypoxia, an important characteristic following TACE, can trigger chemoresistance to doxorubicin in HepG2 cells [18].…”
Section: Introductionmentioning
confidence: 89%
“…As yet, no thresholds have been established for assessing the extent of the periablational zone based on Ω. However, although there is still no accurate assessment of the scope of this entire area, there do exist experimental data that provide some insight on the subject and may be used as a guide in selecting suitable thresholds; for example, the study by Markezana et al [ 1 ] reports a statistically significant accelerated growth of tumor cells subjected to moderate hyperthermia, especially when heated to 43 and 45 °C for 5 and 10 min. We used these four combinations of temperature–time values to estimate the range of Ω to define the periablational zone by means of the Arrhenius damage model with the following parameters: frequency factor A = 7.39×10 39 s −1 and activation energy Δ E = 2.577×10 5 J/mol [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…As 55% of cells are still viable at a damage index of Ω=0.6 and 12% at Ω=2.1, this means that the periablational zone includes both viable cells and those damaged by heating, which can range from around 55% at Ω=0.6 to 88% at Ω=2.1. It must be recognized that the entire periablational zone is composed of cells subjected to moderate hyperthermic heating and is not necessarily limited to the thermal doses considered by Markezana et al [ 1 ], and that if different Ω values were to be found in future studies this would mean redefining the periablational zone and changing some of the conclusions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations